APPLICATION OF THE ENTROPY–MARCOS METHOD IN A DECISION SUPPORT SYSTEM FOR SELECTING TOURIST DESTINATIONS IN SEMARANG - Eka Yulianti Ekayulianti; Saifur Rohman Cholil (Jurnal Riset Informatika, 2026)
Tourism is an important sector that supports regional economic growth. In the Semarang area, the increasing number of tourist destinations provides many options for visitors, but it can also make it difficult for tourists to determine the most appropriate destination based on several considerations. Therefore, this study aims to develop a decision support system for selecting tourist destinations using a multi-criteria decision-making approach. The criteria used in this study include travel time, ticket price, tourist facilities, and destination rating. The data were obtained from digital tourism information and questionnaire responses from 64 respondents. The Entropy method was used to determine objective criteria weights based on data variation, while the MARCOS method was applied to rank tourist destination alternatives based on their proximity to ideal and anti-ideal solutions. The results show that Kota Lama is the most recommended tourist destination with the highest final score, followed by Lawang Sewu and Pagoda Avalokitesvara. The validation results using Spearman correlation analysis produced a coefficient value of 0.9879, indicating a very strong agreement between the ranking results generated by the Entropy–MARCOS model and tourist preference rankings. This study contributes by integrating objective weighting and ranking methods using digital tourism data to provide a structured approach for tourism decision support systems.